DESIGN AND THE ANALYSIS OF SIX-DEGREE-OF-FREEDOM ADJUSTING MECHANISM WITH HIGH ACCURACY AND STIFFNESS - HE Lei; HAN HasiaoQier; HAN ChunYang; HE Shuai; CHEN LiHeng (Jixie qiangdu)
A precision adjusting mechanism of six-degree-of-freedom（SDOF）based on Stewart structure with high accuracy and high stiffness is designed in this paper. Firstly, the configuration of adjusting mechanism was designed and the kinematics analysis was conducted; Then, the error model was established and the precision of the configuration of parallel platform was analyzed. After that, the structure of adjusting mechanism was designed according to the theoretical analysis results, including the single displacement actuator and the offset hinge; Finally, the stiffness of the adjusting mechanism was analyzed. This article obtaining the analysis results that the repeatability of the SDOF adjusting mechanism were ±2 m in X and Y direction,±0.54 m in Z direction, ±6.13 rad in Rx, Ry, Rz direction, and the fundamental frequency of the transverse vibration was 104.3 Hz and the axial stiffness was 61.3 N/μm. The analysis results showed that the SDOF precision adjusting mechanism fulfilled the design requirements, and the rationality for structure design of adjustment mechanism was verified.